Inter-method reliability for determining total and soluble fluorides in child low-fluoride formula dentifrices - Bijle, Mohammed Nadeem (Sci Rep, 2020)
The study aimed to compare three methods for determining total (TF) and total soluble fluorides (TSF) in 5 child formula dentifrices (CFD) using Inter-method reliability (IMR) statistical approach. The methods were direct acid-hydrolysis (DM), the least-time-consuming method; Modified direct acid-hydrolysis with standard-addition method (MDM), ISO 19448:2018 method; and modified Taves acid-HMDS diffusion analysis (TAD), the claimed gold standard method. A significant difference in the mean difference was observed for all methods at all levels (p < 0.001), except DM and TAD for TF (p = 0.622). A proportional bias was discerned in the agreement distribution between DM and TAD for TF (p < 0.001). The ICC analysis identified significant reliability between all measurements, irrespective of the model, measure, and fluoride type (p < 0.001). For TF and TSF, the IMR between DM and TAD was lower than MDM and TAD for consistency/absolute agreement reliability at single/average measures. The reliability measure for DM and MDM was higher than MDM and TAD for TSF, but was lower than MDM and TAD for TF. The ICC measure for DM-TAD was significantly lower than DM-MDM and MDM-TAD (p < 0.05). The ISO 19448:2018 MDM is a reliable test that can be used as an alternative to TAD/DM for determining TF/TSF in CFD.